Wide-nosed pygmy grasshoppers (Cladonotinae: Cladonotini, Xerophyllini) of India and Sri Lanka: catalogue with an identification key and description of a new species of the genus Tettilobus - Bhaskar, Dhaneesh; Stermšek, Sara; Easa, P.s.; Franjević, Damjan; Skejo, Josip (Zootaxa, 2020)
Wide nosed pygmy grasshoppers (Tetrigidae: Cladonotinae) are grasshoppers in which the frontal costa bifurcates into strongly divergent facial carinae, between which there is wide scutellum. Altogether seven genera and thirteen species inhabit India and Sri Lanka. Tribe Cladonotini is represented in this region by five genera and nine species (Cladonotus—4 spp., Deltonotus—2 spp., Gignotettix—1 sp., Hancockella—1 sp., and Yunnantettix—1 sp.), while the tribe Xerophyllini by two genera, Tettilobus (3 sp.) and Potua (1 sp.). For this Potua species it is not clear if it belongs to this genus. A simple identification key to Cladonotinae of India and Sri Lanka is provided. New synonyms are: Deltonotus humilis syn. nov., Epitettix tamilus syn. nov. and Potua aptera syn. nov., synonymous with Deltonotus gibbiceps. Deltonotus cristatus should be regarded nomen nudum. A new species, assigned to the genus Tettilobus is described from the Western Ghats of Kerala, Tettilobus trishula Skejo, Bhaskar et Stermšek sp. n. Furthermore, we present the first records of D. subcucullatus from India (Kerala).